Pengaruh Dosis Nitrogen Berbasis Pupuk Organik Limbah Ampas Kopi dan Macam Media Tanam Terhadap Pertumbuhan dan Hasil Tanaman Sawi (Brassica juncea L.) - Sunartadi, Difa Rosalina; Widjajanto, Didik Wisnu; Purbajanti, Endang Dwi (JURNAL AGROPLASMA, 2023)
This study was aimed to examine the effect of nitrogen-based fertilizers based on coffee grounds and types of planting media on the growth and yield of mustard greens (Brassica juncea L.). The research was carried out on October 03, 2021 – March 20, 2022, at the Green House and at the Ecology and Plant Production Laboratory, Faculty of Animal and Agricultual Sciences, Diponegoro University, Semarang. The factorial experiment with a 4 x 3 completely randomized design with 3 replication was used in the study. The first factor (P) consist of 4 levels of nitrogen dose based on coffee grounds organic fertilizer (CGOF) , namely P0 = control, P1 = 150 kg N/ha equivalent to 10,5 tons CGOF/ha, P2 = 170 kg N/ha equivalent to 11,9 tons CGOF/ha and P3 = 190 kg N/ha equivalent to 13,3 tons CGOF/ha. The second factor (M) consists of several kinds of planting media, namely M1 = soil, M2 = soil + husk charcoal (3:1) and M3 = soil + cocopeat (3:1). The recommended dose of nitrogen used in the study was 170 kg N/ha. The parameters observed were plant height, number of leaves, root length, fresh weight, plant dry weight, harvest index and root crown ratio. The data obtained were tested using the Analysis of Variance (ANOVA) and the results that significantly affected the observed parameters were then further tested using Duncan’s Multiple Range Test (DMRT) at the level 5%.Keywords: dose, nitrogen, coffee grounds, mustard greens.